Qualitative analysis of the concept and practice of comprehensive rehabilitation perceived by stakeholder actors (2016)
Introduction: Comprehensive rehabilitation is a difficult concept since it is the result of historical evolution. Objective: To present the findings of the study “Access to comprehensive rehabilitation services in Colombia: an approach from the concepts and practices of different social actors”, and to describe the perception of comprehensive rehabilitation based on the opinions of different actors from a comprehensive perspective of disability. Material and methods: A descriptive and exploratory, qualitative study was conducted, taking into account multiple sources of evidence to identify the perceptions of actors responsible for formulating and implementing public policies (PP), academicians (A), professionals (P), representatives of social organizations (SO), service managers (SM), service managers and professionals in inclusive education (IE), persons with disabilities (PWD) and caregivers (C), involved in comprehensive rehabilitation in a Colombian city. 18 interviews with actors were conducted; six focus groups were developed. For data analysis, the Atlas ti® software, the agreement between judges and the analysis of narratives were considered. Results: Comprehensive rehabilitation is perceived differently by the actors, and three conceptions are relevant: it is a result of a functional rehabilitation process; it is a right, and it is also a guarantor of social inclusion. Conclusions: While there is diversity and dispersion in opinions on comprehensive rehabilitation, it will be difficult to conceive, implement, evaluate and actively participate in this process. Consequently, access barriers will increase and it will be far from understood as a right exercised from an integral vision of the human being. With this in mind, implications for academia, service providers and public policies are set. © 2016, Universidad Nacional de Colombia. All rights reserved.